2019
DOI: 10.21203/rs.2.13234/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge On Neonatal Danger Signs And Associated Factors Among Mothers Who Gave Birth In The Last One Year Prior To This Study In Debre Markos Town, East Gojjam, Northwest Ethiopia 2017: A Community Based Cross Sectional Study.

Abstract: Background: Neonatal mortality is a concern for global population especially in developing countries. The majority of neonatal mortality occurs at home where only few families recognize key danger signs of neonatal illness. Thus, we assessed the knowledge on neonatal danger signs of illness and associated factors among mothers who gave birth in the last one year prior to this study in Debre Markos town, East Gojjam, northwest Ethiopia. Methods: A community-based, cross-sectional study was conducted among 521 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Furthermore, various studies indicated that knowledge of neonatal danger signs had a significant association with the treatment-seeking behavior of the mothers [18,22]. However, in Ethiopia, besides the attempts made to scale-up the maternal and child health services, maternal knowledge of neonatal danger signs remains low [10,11,12,13,15,16,17,18,19,20,21,23]. Therefore, this study aimed to assess the knowledge of neonatal danger signs and associated factors among mothers attending pediatric immunization clinics in Gidan district health centers, North Wollo, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, various studies indicated that knowledge of neonatal danger signs had a significant association with the treatment-seeking behavior of the mothers [18,22]. However, in Ethiopia, besides the attempts made to scale-up the maternal and child health services, maternal knowledge of neonatal danger signs remains low [10,11,12,13,15,16,17,18,19,20,21,23]. Therefore, this study aimed to assess the knowledge of neonatal danger signs and associated factors among mothers attending pediatric immunization clinics in Gidan district health centers, North Wollo, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, various factors that had a significant association with maternal knowledge of neonatal danger signs were also identified. Of these, age, occupation, maternal level of education, fathers' educational level, residence, availability of Radio or Television (TV), antenatal care (ANC) follow-up, spousal involvement during ANC, place of delivery, postnatal care (PNC) follow-up, higher decision-making ability, birth preparedness, information about neonatal danger signs, gravidity, previous experience of neonatal danger signs (NDSs), and counseling on newborn care are among them [9,10,11,12,13,14,15,16,17,18,19,20,21]. Early identification of neonatal danger signs is an important step toward improving newborn survival [15].…”
Section: Introductionmentioning
confidence: 99%